2018
DOI: 10.1371/journal.pone.0195810
|View full text |Cite
|
Sign up to set email alerts
|

A low dose lipid infusion is sufficient to induce insulin resistance and a pro-inflammatory response in human subjects

Abstract: ObjectiveThe root cause behind the low-grade inflammatory state seen in insulin resistant (obesity and type 2 diabetes) states is unclear. Insulin resistant subjects have elevations in plasma free fatty acids (FFA), which are ligands for the pro-inflammatory toll-like receptor (TLR)4 pathway. We tested the hypothesis that an experimental elevation in plasma FFA (within physiological levels) in lean individuals would upregulate TLR4 and activate downstream pathways (e.g., MAPK) in circulating monocytes.Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
1
23
0
2
Order By: Relevance
“…During obesity, the pro-inflammatory cytokines IL-1β and TNF-α can interfere directly with insulin signaling in adipocytes (Liang et al, 2018). We observed that IL-1β expression in the OBF group did not differ from C and OB groups, while TNF-α levels were similar between all groups (C, OB, OBF and OBP) (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…During obesity, the pro-inflammatory cytokines IL-1β and TNF-α can interfere directly with insulin signaling in adipocytes (Liang et al, 2018). We observed that IL-1β expression in the OBF group did not differ from C and OB groups, while TNF-α levels were similar between all groups (C, OB, OBF and OBP) (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…According to the literature,20 insulin secretion is a complex process with various influencing factors, and FFA metabolism may exert double-sided effects on this course. FFA, at relatively low levels, functions as an energy source to provide ATP.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that acute hyperinsulinemia and hyperlipidemia, characteristic of metabolic syndrome, significantly decreases LH and FSH in normal weight women, providing a possible mechanism underlying the hypergonadotropic hypogonadism of obesity [ 6 ]. Others have shown that a very similar infusion of non-esterified fatty acids and insulin in lean research participants can result in insulin resistance and elevated TNF-alpha, although circulating cytokines were studied only after 48 hours [ 16 ]. Use of a multiplex cytokine array allowed profiling of a comprehensive panel of diverse markers of inflammation, given the limited serum samples available.…”
Section: Discussionmentioning
confidence: 99%